Una aproximación a la tuberculosis resistente a isoniazida: ¿un problema subestimado en Colombia? - José Fernando García-Goez (Asociación Colombiana de Infectología, 2020)
Objective: To describe the clinical characteristics and outcomes to the treatment of patients with isoniazid-resistant tuberculosis (Hr-TB) in an institution in southwest Colombia. Materials and methods: A retrospective observational study was conducted. Patients with diagnostic confirmation, microbiological isolation, drug susceptibility tests, and evidence of Hr-TB were included. Results: Thirty-two patients with Hr-TB were included between 2006-2018, corresponding to 6% (32/528) of resistance in total cases. 78% were new cases, primary resistance, and 22% previously treated, acquired resistance. The most frequent comorbidity was HIV infection (n = 9). The pattern of Hr-TB showed in 23 (72%) cases with high level, 4 (12%) of low level and 5 (16%) with low and high level. The analysis of treatment results was performed on 22 patients, presenting 50% cure, 41% completed treatment, and 9% death related to tuberculosis. Conclusions: Hr-TB predominates in new cases, which is an obstacle to treatment where susceptibility tests are not performed routinely.